Equivalent crack size model for pre-corrosion fatigue life prediction of aluminum alloy 7075-T6. (July 2016) - Huang, Yongfang; Ye, Xubin; Hu, Benrun; Chen, Lijie
Highlights: Fatigue crack initiates from a single pit or pit cluster at the central hole. For single-crack cases ar ECS vs. ar cri is best correlated with coefficient of 0.9. For multi-crack cases ar ECS vs. r cri is best correlated with coefficient of 0.69. ECS models are developed with the best relevant metrics ar ECS  ∼  ar cri and ar ECS  ∼  r cri . N pre predicted with ECS models agree well with N exp with the error factor of 1.6. Abstract: Corrosion damage can significantly reduce the service life of aluminum alloy structures and endanger the structural integrity of aircraft. Here, aiming at center-hole sheet specimens of aluminum alloy 7075-T6, uniaxial fatigue tests and post-fracture analysis are performed to investigate the effect of corrosion pits on the pre-corrosion fatigue behavior. Then the best correlated parameters between corrosion pits and equivalent cracks are identified through Pearson correlation analysis. It is found that for single-crack initiations ar ECS (equivalent crack depth ∗ aspect ratio) vs. ar cri (critical pit depth ∗ aspect ratio) are best correlated with correlation coefficient of 0.9, while the best correlated parameters for multi-crack initiations are ar ECS (equivalent crack depth ∗ aspect ratio) vs. r cri (aspect ratio) with correlation coefficient of 0.69. Equivalent crack size (ECS) models are correspondingly developed with these best correlated parameters for single- and multi-crack initiations, respectively. The pre-corrosion fatigue lives predicted with our models agree well with the experimental results and the maximum error factor is about 1.6.